The effectiveness of psychological counseling in relieving alexithymia (difficulty expressing feelings) in children with reading difficulties - Karim Al-Sharhan, Fawaz Adel Abdul (International Journal of Psychosocial Rehabilitation, 2025)
The prevalence of alexithymia, as well as the prevalence of learning difficulties in general and reading difficulties in particular varies, and the effect of this behavior on learning difficulties is clear. Through the researcher’s work and his knowledge, it was found that the fear of students with learning difficulties from expressing their feelings and being terrified, which has a negative impact on their general lives, which reduces their mixing with their fellow students and makes them feel completely isolated, which affects their academic achievement, behavior and social compatibility. Therefore, the aim of the research is to know the effect of Psychological counseling for the development of expressive language and its effect on reducing the symptoms of alexithymia among students with reading difficulties. The research sample consisted of (52) students with reading difficulties, (24) control groups, and (28) experimental groups, whose ages ranged between (10-11) years. The research tools included: The Diagnostic Assessment Scale for Reading Difficulties, the Speech and Language Scale in the Kuwaiti Dialect, which is standardized in the Kuwaiti environment for Professor Maryam Sami Jojo. The results of the research concluded that there are statistically significant differences at the level (0.01) between the mean scores of the experimental group members in each From the pre and post measurements on the expressive difficulties scale for children in the direction of the dimensional measurement, that is, the average scores of the experimental group members in the post measurement are statistically higher than their counterpart in the pre measurement, where the value of (Z) reached (- 3.71), which is a statistically significant value at the level of (0. 01), there are statistically significant differences at the level (0.01) between the average scores of the members of the experimental group after applying the program and the average scores of the members of the control group after applying the program on the scale of expressive difficulties in the direction of the experimental group, meaning that the average scores of the experimental group members in the post-measurement are higher In statistical terms of its counterpart in the control group, where the value of (Z) was (-2.34), which is a statistically significant value at the level of (0.01), there are no statistically significant differences between the mean scores of the individuals in the experimental group in each of the The two measurements of the dimension and the tracer on the expressive difficulties of children, that is, the average scores of the members of the experimental group in the post measurement in the expressive difficulties are equal in statistical significance to the counterpart in the tracer measurement, where the value of (Z) (-1.01) is a non- statistically significant value. By discussing the results, the researcher concluded that various behavioral programs must be supported and programs should be prepared that help in developing the behavior of children with learning difficulties, provide families with programs, courses and methods of dealing with people with learning difficulties, and activate the role of the media in educating society on the interest and positive interaction with this category.